Multifocal cocaine-induced pyoderma gangrenosum: A report of two cases and review of literature. (August 2020) - Lemieux, Alexandre; Ran Cai, Zhuo; Belisle, Annie; Chartier, Suzanne; Bolduc, Chantal
Pyoderma gangrenosum is often associated with a systemic disease. Cocaine-induced pyoderma gangrenosum, most probably caused by levamisole, has been described recently and typically presents as multiple, large cribriform ulcers. Peri-nuclear antineutrophil cytoplasmic antibody is the most common serological finding. A strong counseling for cocaine cessation, combined with wound care and immunosuppressive therapy, is the mainstay of treatment. We present two cases of cocaine-induced pyoderma gangrenosum and correlate their findings with the typical clinical, histological and serological presentation.